Struktur Iklan Baris Penjualan Rumah dalam Surat Kabar Solopos Edisi November 2015 - Februari 2016 dan Implementasinya di SMP - Lestari, Nuri; , Drs. Agus Budi Wahyudi, M.Hum (2017)
The purpose of this study was to describe: (1) Describe the structure of classified ads home sales in newspapers Solopos edition November 2015 - February 2016, (2) to describe a form of structure classifieds home sales in newspapers Solopos edition November 2015 - February 2016, and (3)Describe the relationship between the structure home sales classified ads in newspapers Solopos edition November 2015 - February 2016 and its implementation in SMP. This study used descriptive qualitative method. The data source of this research is the classified ads in a newspaper home sales Solopos edition November 2015 - February 2016. The data in this study a phrase contained in a classified ad in a newspaper home sales Solopos edition November 2015 - February 2016. The research data collection techniques used engineering library, see the engineering and technical notes. Data were analyzed using methods agih method. The findings of this study indicate that 1) The structure of classified ads home sales in newspapers Solopos edition November 2015 - February 2016, (1) Loading the name of goods or services, (2) Load the type or types of goods or services, (3) Loading condition of the goods or services, 4) Loading facilities goods or services, and 5) Loading address or phone number that can be in contact. 2) The form of the structure home sales classified ads in newspapers Solopos edition November 2015 - February 2016, there are two structures which form a complete and incomplete. 3) The linkage structure home sales in the newspaper Solopos edition November 2015 - February 2016 to the curriculum in 2006 (SBC), because in the curriculum of 2006 (SBC) are SK and KD on advertising in particular in class IX SMP namely SK 4. Disclose information in the form of classified ads, essay, and thoughts and feelings in free verse, and KD 4.1 Write a classified ad in a language that is concise, solid and clear